Bahasa dan Narasi Politik Kreatif; Kontestasi Merebut Kebenaran Islam dalam Demokrasi Digital 2019 di Indonesia - Putra, Wahyu Hanafi; Rohmatulloh, Dawam M. (Proceedings of Annual Conference for Muslim Scholars, 2019)
This study aims to describe the language and narrative of creative politics that are contested in order to seize the truth of Islam in the 2019 electoral-digital democracy in Indonesia. The research method used is descriptive-qualitative. The data and sources of research data used are the latest research in a three-year cycle related to identity politics and the politicization of religion. Orwell (1950) considers that language can be used to influence and change political ideology and change the way of thinking of others. The results of this study indicate that the political correctness leading up to the 2019 electoral democracy party in Indonesia is characterized by religious populism that is publicized on social media such as flyers, memes, hashtags, and Muslim Cyber ​​Army (MCI) affiliated accounts. The existence of social media accounts with creative language narratives has changed people's perceptions and ideologies that have an impact on destructive behavior, racism, anarchism, and intolerance in seizing the truth of Islam in political contestation